From current distinctiveness to future homogenization of the world's freshwater fish faunas. Issue 2 (25th August 2014) - Villéger, Sébastien; Blanchet, Simon; Beauchard, Olivier; Oberdorff, Thierry; Brosse, Sébastien; Jeschke, Jonathan
Abstract Aim Assessing the consequences of a future increase in non‐native species introductions and native species extirpations on taxonomic similarity among fish faunas. Location World‐wide. Methods We designed 42 scenarios of future species introductions and extirpations to simulate future fish composition for 1054 river basins. Using these simulated future compositions, we computed the change in taxonomic similarity among pairs of fish faunas from historical to future situation at the river basin, biogeographic realm and world scales. Results According to all our scenarios, taxonomic similarity among fish faunas will strongly increase in the future at the three spatial scales considered. Fish faunas from the Southern Hemisphere, which are currently the less affected by taxonomic homogenization, are forecasted to show the steepest changes. Our scenarios also reveal that non‐native species introductions will account for most of the predicted changes, whereas the effect of native species extirpations will be weak. Main conclusions The predicted future taxonomic homogenization will blur the current high level of taxonomic dissimilarity among freshwater fish faunas, and therefore, imperil the conservation programmes based on beta‐diversity mapping.